CARDIORESPIRATORY FITNESS (CRF) IN HEALTHY, ASYMPTOMATIC, AND SYMPTOMATIC COVID-19 SUBJECTS - Iskandar, Roni
Background: COVID-19 has not only caused a health crisis, but all aspects of life. Preventive measures of medical sector have high hopes for the vaccine findings, but until now there has not been found a vaccine that is truly effective in helping individuals avoid COVID-19. Beside medical perspective, sport health in this case cardiorespiratory fitness (CRF) as an attribute of individual fitness also have an important role in the spread of COVID-19. The multisystemic effect of COVID-19 can decrease CRF. There is a strong relationship between CRF and the normal or optimal functioning of the immune system. Study Long et al. (2020) concluded that individuals asymptomatic of COVID-19 had a weaker immune response to SARS-CoV-2 infection due to the discovery of a small number of immune components; but contrary to the conclusions of the study of Le Bert et al. (2021) that asymptomatic individuals mount a highly functional viral-specific immune response. Objective: The aims of this study was to compare CRF of subjects infected COVID-19 with healthy subjects and determine a person's CRF levels so that an individual is immune or infected COVID-19 produces a minimum effect. Methods: Asymptomatic subjects (n = 10) and symptomatic (n = 10) were evaluated and compared with healthy subjects (n = 10). Data for age, gender, anthropometry, blood pressure, 02 saturation of all participants were collected and analyzed, then all participants were asked to take the Rockport Walking Test, completion time and heart rate as soon as the test was measured. Result: Symptomatic (GJ) subjects presented lower CRF than asymptomatic (OTG) and healthy (S) subjects (p < 0.05 for all comparisons). Asymptomatic subjects showed higher CRF than symptomatic subjects (p < 0.05) and healthy subjects (p > 0.05). Conclusion: Asymptomatic subjects of COVID-19 present high cardiorespiratory fitness even higher than healthy subjects. This shows that the immune system of asymptomatic subjects works optimally to eliminate SAR-CoV-2 virus as the causative agent of COVID-19. The recommended cardiorespiratory fitness level of this study for being immune to COVID-19 was 42.0+2.6 mL.kg-1 min' (above average normative) for men (age 39.5+7.7 years) and 34.3+3.2 mL.ke (above average normative) for women (age 41.5+9.1 years).